Physics, chemistry, and application of nanostructures : (World Scientific, 2005)
This comprehensive volume presents invited reviews and short notes with exciting new results obtained in fabrication study and application of nanostructures, which promise a new generation of electronic and optoelectronic devices. The rapid progress in nanoelectronics and optoelectronics, molecular electronics and spintronics, nanotechnology and quantum processing of information are covered.